Review of the Predictive Value of Biomarkers in Sepsis Mortality - Nai Zhang; Yujuan Liu; Chuang Yang; Xinai Li (Emergency Medicine International)
Sepsis is a leading cause of mortality among severely ill individuals, primarily due to its potential to induce fatal organ dysfunction. For clinicians, it is vital to have appropriate indicators, including the physiological status and personal experiences of patients with sepsis, to monitor the condition and assess prognosis. This approach aids in preventing the worsening of the illness and reduces mortality. Recent guidelines for sepsis focus on improving patient outcomes through early detection and timely treatment. Nonetheless, identifying severe cases and predicting their prognoses remain challenging. In recent years, there has been considerable interest in utilising the C-reactive protein (CRP)/albumin ratio (CAR) to evaluate the condition and forecast the prognosis of patients with sepsis. This research concentrates on the significance of CAR in the pathological process of sepsis, its association with prognosis, and the latest developments in employing procalcitonin, lactic acid, CRP, and other potential biomarkers. The CAR, with its predictive value for sepsis prognosis and mortality, is increasingly used as a clinical biochemical marker in diagnosing and monitoring patients with sepsis.